The humanistic and economic burden associated with increasing body mass index in the EU5 - Gupta, Shaloo (Diabetes Metab Syndr Obes, 2015)
OBJECTIVES: This study evaluated the association of body mass index (BMI) with health-related quality of life (HRQoL), health utilities, health care resource utilization, productivity, activity impairment, and the associated costs. METHODS: Results were from the 2013 EU5 (France, Germany, Italy, Spain, UK) National Health and Wellness Survey, a nationally representative, online survey of respondents aged ≥18 years. Analyses focused on normal weight (BMI ≥18.5 kg/m(2) and BMI <25 kg/m(2)), overweight (BMI ≥25 kg/m(2) and BMI <30 kg/m(2)), Obese Class (OC) I (BMI ≥30 kg/m(2) and BMI <35 kg/m(2)), OC II (BMI ≥35 kg/m(2) and BMI <40 kg/m(2)), and OC III (BMI ≥40 kg/m(2)) respondents. Outcomes included HRQoL (Short Form [SF]-36v2), health utilities (SF-six dimension [6D]), productivity loss (Work Productivity and Activity Impairment questionnaire), and resource utilization (provider visits, emergency room visits, and hospitalizations) in the past 6 months. Direct and indirect costs were estimated from the literature. Generalized linear regression models predicted outcomes as a function of BMI, adjusting for covariates (age, sex, comorbidities). RESULTS: Among 58,364 respondents, 46.9% were normal weight, 34.5% were overweight, 12.5% were OC I, 4.0% were OC II, and 2.1% were OC III. Metabolic comorbidities increased as BMI increased. After adjustments, all three OC respondents exhibited significantly lower HRQoL than normal weight respondents. Health utilities (normal weight: 0.720; overweight: 0.718; OC I: 0.703; OC II: 0.683; OC III: 0.662) declined with an increase in BMI (all P<0.05 vs normal). Among employed respondents (57.7%), overall work impairment increased as BMI increased. Normal (vs all OCs) had lower activity impairment and fewer provider visits, lower indirect costs (normal weight: €7,974; overweight: €7,825; OC I: €8,465; OC II: €9,394; OC III: €10,437), and lower total direct costs (normal weight: €516; overweight: €553; OC I: €583; OC II: €605; OC III: €717), all P<0.05. CONCLUSION: Increased BMI was associated with worse HRQoL, greater comorbidities, higher direct and indirect costs, and worse health utilities. Weight management may improve patient outcomes.